Assessment of Reagents for Selenocysteine Conjugation and the Stability of Selenocysteine Adducts - Pedzisa, Lee (Org Biomol Chem, 2016)
Conventional antibody-drug conjugates (ADCs) are heterogeneous mixtures that have poor pharmacokinetic properties and decreased efficacy relative to homogenous ADCs. Furthermore, ADCs that are maleimide-based often have inadequate circulatory stability, which can result in premature drug release with consequent off-target toxicities. Selenocysteine-modified antibodies have been developed that allow site-specific antibody conjugation, yielding homogeneous ADCs. Herein, we survey several electrophilic functional groups that react with selenocystine with high efficiency. Several of these result in conjugates with stabilites that are superior to maleimide conjugates. Among these, the allenamide functional group reacts with notably high efficiency, leads to conjugates with remarkable stability, and shows exquisite selectivity for selenocysteine conjugation.